Judicial review of commercial regulation - Arancibia, Jaime (Oxford : Oxford University Press, 2011)
Examining the law of judicial review in the context of commercial regulation, this book provides a critical view of British courts' deferential attitude to commercial regulation. It advocates a more intensive form of review based on the principle of proportionality which is more satisfactory in terms of individual justice.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Commercial law -- England; Commercial law -- Wales; Judicial review -- England; Judicial review -- Wales